Probing the B- & C-rings of the antimalarial tetrahydro-β-carboline MMV008138 for steric and conformational constraints. Issue 22 (15th November 2020) - Ding, Sha; Ghavami, Maryam; Butler, Joshua H.; Merino, Emilio F.; Slebodnick, Carla; Cassera, Maria B.; Carlier, Paul R.
Graphical abstract: Abstract: The antimalarial candidate MMV008138 (1a ) is of particular interest because its target enzyme (IspD) is absent in human. To achieve higher potency, and to probe for steric demand, a series of analogs of 1a were prepared that featured methyl-substitution of the B- and C-rings, as well as ring-chain transformations. X-ray crystallography, NMR spectroscopy and calculation were used to study the effects of these modifications on the conformation of the C-ring and orientation of the D-ring. Unfortunately, all the B- and C-ring analogs explored lost in vitro antimalarial activity. The possible role of steric effects and conformational changes on target engagement are discussed.